Ability to Write a Reader’s Letter About the School Environment in 03 Lumbir State Junior High School - Nur Amalia Solikhah; Destia Herlisya (CV. Tripe Konsultan, 2021)
The issues examined in this research relates to the ability of students in writing letters of readers about the school environment. This research uses descriptive quantitative methods, and sampling techniques used are random class (cluster random sampling). Engineering data collection using the technique of main performance writing letters readers about the school environment. Technique of data analysis using quantitative analysis with the descriptive approach. Based on research results, gained that ability of students in writing letters of readers about the school environment belongs simply because final value shows number 67. The constraints experienced by students in writing letters of readers about the school environment i.e. students still lack understanding about the reader's letters, and the difficulty of applying aspects of mail readers. The most prominent barriers in writing letters of readers about the school environment experienced by students i.e. difficulty applying the spelling language Indonesia with good and true.